Strategy For Implementing Online Learning In Bengkulu - Sumarsih Sumarsih (Universitas Ahmad Dahlan, 2022)
The purpose of this study was to describe the strategy for implementing online learning at Public vocational secondary schools Bengkulu Utara Regency. This research is a qualitative descriptive study. The research subjects were the principal, teachers, and students. Data collection techniques using interviews and documentation. The results showed that online learning strategies were implemented using a variety of methods between meetings using zoom meetings, video calls. giving assignments via WhatsApp, PowerPoint, youtube, and giving weekly assignments. While the obstacles lack of motivation to learn, lack of discipline in doing assignments, lack of understanding of the material, high parental credit costs, internet network disruption. Solutions made by schools increase teacher knowledge through training, teacher group discussion forums.